Deciphering the ocean bottom pressure variation in the Logatchev hydrothermal field at the eastern flank of the Mid-Atlantic Ridge - Gennerich, Hans-Hermann; Villinger, Heinrich (GEOCHEMISTRY GEOPHYSICS GEOSYSTEMS, 2011)
Ocean bottom pressure data from the Logatchev hydrothermal field (LHF) are presented and analyzed. The data were collected with two ocean bottom pressure meters (OBPs), constructed at the University of Bremen, that are capable of recording signals with frequencies up to 0.25 Hz. Over the long-term, a nearly 2.5 kPa (25 cm water column equivalent) pressure variation over 3.7 years is observed, which is consistent with uplift followed by subsidence, but cannot unequivocally be discerned from instrumental drift. Medium-term pressure variations are compared with satellite surface topography, satellite gravity, ocean modeling, and in situ data from an OBP 700 km away. It is shown that fluctuations in the oceanic mass distribution dominate the variations in this frequency range and that oceanic modeling and data from a 700 km distant OBP are positively correlated with the LHF bottom pressure time series. The short-term variations are dominated by microseisms originating from sea surface waves and pressure waves from earthquakes as can be shown by comparison with weather buoy and teleseismic data.
Keywords: ROV Jason (Remotely Operated Vehicle)